Feasibility of Unilateral Approach for Bilateral Decompressive Endoscopic Spinal Surgery for Lumbar Stenosis to Improve Back and Leg Pain: A Consecutive Single-Center Series of 60 Patients - Salim, Azizul Akram; Yusof, Abdul Halim; Johari, Joehaimey; Yusof, Mohd Imran (Frontiers in Surgery, 2020)
Introduction: Endoscopic surgery is one of the methods that achieve the goal of decompression while minimizing collateral tissue damage. Its efficacy and safety have been supported by numerous studies. There is a plethora of studies on lumbar stenosis regarding the outcomes and related issues in endoscopic spine surgery. However, few studies evaluated the outcome of the decompressive lumbar spine surgery. The present study aims to analyze the outcome of a unilateral approach to endoscopic surgery for lumbar stenosis using the visual analog scale (VAS), the Oswestry Disability Index (ODI), and MacNab’s criteria. Materials and Methods: This is a retrospective study (Level IV) conducted between January 2009 and December 2013 on 60 patients who underwent endoscopic interlaminar decompressive spine surgery (Destandau’s method) for lumbar degenerative spinal stenosis in the Hospital Universiti Sains Malaysia. The clinical outcome was measured preoperatively and postoperatively for VAS; for back and leg pain, motor and sensory grading, the ODI, and MacNab’s criteria. A paired t-test was used for statistical analysis. Results: The mean age of patients was 60.82 years comprising 23 (38.3%) males and 37 (61.7%) females. The mean follow-up period was 30.1 months (range 17.2 to 43 months). The mean operation time was 183.6 min (ranging from 124.8 to 242.4 min) and the mean blood loss was 150.18 ml (ranging from 30.82 to 269.54 ml). Postoperatively mean hospital stay was 2.45 days (ranging from 1.34 to 3.56 days). The most frequently involved level was L4/L5 in 51 patients (52.6%), followed by L3/L4 in 19 patients (19.6%), L5/S1 in 24 patients (24.7%), and L2/L3 in three patients (3.1%). Improvement in the postoperative VAS for back and leg pain and the ODI for pre- and post-operation were statistically significant (p < 0.001). Conversely, the reduction in neurological status was statistically insignificant. Based on MacNab’s criteria, 88.4% showed excellent to good outcomes. Conclusion: To summarize, unilateral percutaneous endoscopic spine surgery to achieve the bilateral decompression in lumbar stenosis provides excellent yet safe and effective outcomes. It improves back and leg pain and patients’ function significantly.